Religion of the Father? Judaism, Anti-Judaism, and the Family Romance - Bielik-Robson, Agata (Romanica Silesiana)
One of the most common clichés of our culture defines Judaism as the “religion of the Father.” For some this is just a neutral description referring to the fatherly aspect of the Jewish God; for others this is the very epitome of the patriarchal prejudice which privileges the masculine Father Figure at the expense of everything maternal. In my essay, however, I would like to challenge this staple association, by pointing to the simple fact that Jews themselves very rarely – if ever – describe their religion in openly patriarchal terms. In fact, when described in psychoanalytic terms, the role of the Father is here merely transitory: he is to inaugurate a series of subsequent detachments, starting from the disintegration of the first bonds of love (to maternal body and, more generally, to the body of nature) and ending with the complete neutralisation of the “family romance.” The Father Figure, therefore, is called upon only to counteract the power of the primordial “attachments” and initiate a process of separation which will allow the subject to establish himself as a free and mature moral agent, truly “born” into the world.